Parametric investigation of acetone liquid pool fire experiments on fire characteristics - Robane, Nor Syamimi Amalina; Chong Vui San, Michael; Md Said, Mohamad Syazarudin; Mohd Tohir, Mohd Zahirasri (Elsevier, 2025)
Acetone is best known as the primary ingredient in various industrial and domestic settings, the fire characteristics of acetone pool fire are relatively unknown, thus raising safety concerns about the thermal radiation emission to humans and surroundings. This research focuses on parametric investigations of acetone liquid pool fire in a square-shaped stainless-steel pan with diameters of 10, 20, and 30 cm. A series of experimental works was employed to investigate the effect of different pan sizes of acetone pool fire on the structure of the flame, flame height, flame temperature, heat release rate, mass loss rate, and thermal radiation intensities with various combinations parameters. The outcome of the experimental work has proven that acetone pool fire exhibited luminous and yellow colour with turbulent flame structure. It was discovered that the combustion of larger acetone pool fire consistently resulted in higher flame height, higher temperature, higher mass loss rate, and higher heat release rate. The thermal radiation intensity of acetone liquid pool fire indicated an inversely proportional relation where the intensity reduced with increasing heat flux gauge distance and height from the flame base but increased with increasing pan size. Overall, the outcomes of this research hold potential significance in advancing the formulation of improved fire protection strategies and fostering safer practices in handling acetone.